Critical thinking in education: a systematic review (Revista Innova Educación, 2022)
The purpose of the study was to identify and analyze the contributions made to the development of critical thinking in the educational field. Therefore, the examination corresponds to a systematic review design of basic research. The information was collected using the bibliographic and systematic search of documents in different reliable databases. Twenty articles were selected. From the documentary review, it has been determined that the most prevalent investigations have been quantitative, descriptive, qualitative, and mixed. It was found that the development of critical thinking is essential to becoming a whole person. This implies that the subject can define or fully understand a situation or problem that guides him towards its solution. In this context, as a critical thinker, a student must develop specific capacities that are constantly stimulated so that they can be sufficiently enhanced to become an actual skill.
Keywords: teaching; skills; critical thinking; teaching practices